ADHESION OF ASSISTANCE PROTOCOL ON NASOENTERAL CATHETER FIXATION. (Revista Estima)
Objective: To verify the adherence of the nursing team to a care protocol for the fixation of a nasoenteral catheter, after a health education action. Methods: Quantitative, cross-sectional, field, observational and descriptive study in a hospital in the city of Rio de Janeiro. It consisted of two stages: health education action on a nasoenteral catheter fixation protocol and data collection after health education action, in the form of non-participant observation, using an instrument containing information regarding the presence of fixation, type of fixation, record of the date of the procedure and conditions of fixation of the nasoenteral catheter. Results: Health education actions encompassed the participation of 133 nursing professionals. Of the 123 patients observed, 100% had fixation, the most prevalent being nasal fixation (60.16% / n = 74). In 68.29% (n = 84) there was no date record, 95.93% (n = 118) and 87.80% (n = 108) had good cleaning and adherence conditions, respectively. Conclusion: A satisfactory result was not achieved regarding adherence to the type of fixation and registration of the date of the procedure. Despite the unsatisfactory adherence, there was a high positive correlation between the professionals' adherence to the education actions and the correctness ratio of the type of fixation.